PENGARUH LINGKUNGAN KERJA, MOTIVASI, MASALAH PERSONAL, DAN PELATIHAN TERHADAP KINERJA KARYAWAN SERTA DAMPAKNYA TERHADAP KINERJA ORGANISASI - Fadli Yunadi; Hafasnuddin Hafasnuddin; Ridwan Ibrahim (Departemen Manajemen, Universitas Syiah Kuala, 2017)
AbstractRumah Sakit Umum Daerah (RSUD) Meuraxa Banda Aceh is one of the existing hospitals in Banda Aceh City that provides excellent service and quality to people in need of health services. The services provided by Meuraxa Hospital aim to provide quality services to gain the trust of the community. One effort to win the competition by fixing the structure, process and output that the end result is quality of service quality and quality. The phenomenon of less optimal health services provided is inseparable from the role of human resources are still far from the goal of the company so that the impact on the poor quality of performance Meuraxa Hospital itself. The population of this study were all civil servants (PNS) at Meuraxa Municipal of Banda Aceh City which amounted to 262 people. The large number of samples refers to the number of indicators in this study multiplied by 5 Ferdinand (2004: 110). Because the number of indicators used in this study are 32 indicators, then the minimum number of samples used is 160 respondents. But in this study the number of samples used is 120 people . Hypothesis testing was done by using indicators CR and P. Because of the 9 hypothesis tested in this study have CR value above 1.96 or P value smaller than 0.05, Then all hypotheses tested reject Ho and accept H1. In other words the independence variables have the effect of increasing the dependent variable if only the independent variables can be improved by RSUD Meuraxa management. The results also show that there is no indirect effect of work environment, work motivation, personal problems and training on the performance of RSUD Meuraxa Banda Aceh through the performance of its employees. Keywords: Work Environment, Motivation, Personal Issues, Training, Employee Performance, Performance of Meuraxa Hospital of Banda Aceh City